2002
DOI: 10.1002/1522-2683(200205)23:10<1398::aid-elps1398>3.0.co;2-8
|View full text |Cite
|
Sign up to set email alerts
|

Microchannel DNA sequencing matrices with switchable viscosities

Abstract: We review the variety of thermo-responsive and shear-responsive polymer solutions with "switchable" viscosities that have been proposed for application as DNA sequencing matrices for capillary and microfluidic chip electrophoresis. Generally, highly entangled polymer solutions of high-molar mass polymers are necessary for the attainment of long DNA sequencing read lengths (> 500 bases) with short analysis times (< 3 h). However, these entangled polymer matrices create practical difficulties for microchannel el… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
33
0

Year Published

2002
2002
2013
2013

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 45 publications
(33 citation statements)
references
References 41 publications
(73 reference statements)
0
33
0
Order By: Relevance
“…13) Recent advances in DNA sequencing by capillary and microdevice electrophoresis [197]. [199]. An excellent review of the various types of novel polymers being developed to carry out DNA sequencing in microchannel systems.…”
Section: Discussion: An Annotated List Of Useful Articlesmentioning
confidence: 99%
“…13) Recent advances in DNA sequencing by capillary and microdevice electrophoresis [197]. [199]. An excellent review of the various types of novel polymers being developed to carry out DNA sequencing in microchannel systems.…”
Section: Discussion: An Annotated List Of Useful Articlesmentioning
confidence: 99%
“…Linear gels are viscous additives that provide good separation performance and do not need to be polymerized in the capillary. Issues associated with the introduction of highly viscous materials into narrow-bore capillaries have spawned the use of thermally reversible sieving materials (76)(77)(78), including phospholipid nanogels (36). These materials are introduced into the capillary at a temperature that generates low viscosity and then converted into a highly viscous separation additive in the capillary by changing the separation temperature.…”
Section: CLmentioning
confidence: 99%
“…Thermo-responsive polymers are generally copolymers consisting of hydrophobic and hydrophilic blocks such as polyisopropylacrylamide grafted with PEO chains [76][77][78][79]. The viscosity for a moderately hydrophobic copolymer is high because of formation of entangled networks at room temperature, while it decreases rapidly at temperature higher than a certain critical elevated temperature, where a phase transition occurs [48,[76][77][78][79][80][81][82][83]. It is thus suggested that filling of such a polymer solution is carried out at high temperature, while the separation is performed at low temperature for high resolving power.…”
Section: Polymer Solution For Dna Separationmentioning
confidence: 99%
“…It is thus suggested that filling of such a polymer solution is carried out at high temperature, while the separation is performed at low temperature for high resolving power. A series of linear copolymers of N,N'-dimethylacrylamide (DMA) and N,N'-diethylacrylamide (DEA) with different monomer compositions such as the copolymer consisting of 42% DEA and 58% DMA and that of 53% DEA and 47% DMA have been prepared and tested for DNA separations [80,81]. The authors have pointed out that the resolution decreases with increasing the hydrophobicity of the polymer solution [80][81][82][83].…”
Section: Polymer Solution For Dna Separationmentioning
confidence: 99%